Hubungan tingkat kebisingan terhadap fungsi pendengaran karyawan yang bekerja di Pusat Listrik Tenaga Gas (PLTG) Medan - Emilia Salfi; Adlin A; Tengku Siti Hajar Haryuna; Muzakkir Zamzam (Fakultas Kedokteran USU, 2013)
Introduction : Noise induce hearing loss (NIHL) often occurs in industrial workers, especially in countries that have not implementated a good hearing protection system. World health organization (WHO) estimates 16% of the world’s population endures NIHL caused by occupational exposure to noise.Aim : To determine the relationship of noise level on employees’ hearing function who worked at the gas power plant in Medan. Methods : The study design is descriptive with cross sectional study. This report is obtained 78 employees who meet the inclusion criteria. Data collection was done through interviews, physical examination of the ear with otoscope and hearing assessment with pure tone audiometry.Results : Nine employees (30%) worked at >85 dB suffered from NIHL and 21 employees (70%) didn’t suffer from NIHL. Fourteen employees (29.2%) suffered from NIHL who worked at '3d85 dB and 34 employees (70.8%) didn’t suffer from NIHL. With chi-square test found no significant difference between the noise level in gas power plant with GPAB incident (P = 0.937). Conclusion : There is no relationship of noise level on employees hearing function who worked at the gas power plant in Medan.Keywords : NIH; employee; noise